2017
DOI: 10.1016/j.matdes.2017.01.099
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced erosion performance of cold spray co-deposited AISI316 MMCs modified by friction stir processing

Abstract: The present study reports on the erosion properties of a novel surface engineering process combining cold spray and friction stir processing. Tungsten carbide (WC-CoCr) and aluminium oxide (Al2O3) powders were cold spray co-deposited with AISI316 using a twin powder feed system. The deposited coatings were subsequently friction stir processed to refine and redistribute the reinforcing particles and remove the coating-to-substrate interface layer, thus generating a new metal matrix composite surface. Microstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(25 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…Coatings 2020, 10, 123 9 of 35 break up or dissolve the secondary phase particles in the cold sprayed metal matrix composite (MMC) deposits, leading to considerable improvement in mechanical properties. Incorporating cold spray with FSP is a novel two-stage surface engineering process referred to as 'SprayStir' [56,57]. Table 2 summarizes the previous studies regarding the effects of post FSP on cold sprayed coatings.…”
Section: Friction-stir Processing Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Coatings 2020, 10, 123 9 of 35 break up or dissolve the secondary phase particles in the cold sprayed metal matrix composite (MMC) deposits, leading to considerable improvement in mechanical properties. Incorporating cold spray with FSP is a novel two-stage surface engineering process referred to as 'SprayStir' [56,57]. Table 2 summarizes the previous studies regarding the effects of post FSP on cold sprayed coatings.…”
Section: Friction-stir Processing Treatmentmentioning
confidence: 99%
“…In this case, the FSP parameters should be tailored to better modify the microstructures of cold sprayed MMC coatings. For example, when the rotation speed increased from 900 rpm to 1200 rpm and 1500 rpm, the refinement became more prominent with less ceramic particles visually [57]. Moreover, additional FSP passes through the MMC coatings could also distribute the cold sprayed reinforcing ceramic particles to a greater extent, even to nanoscale [61].…”
Section: Friction-stir Processing Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Even then, the studies employing such concept are limited in the literature and involve successful depositions of W-Cu by Kang and Kang [10] and Deng et al [11], W-Ni-Fe by Xia et al [12], and low tungsten content in W-90Ta coatings by Barnett et al [13] only. Considering their excellent wear properties, a significantly broader series of studies involved the research of cemented carbides in a form of WC-Co [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], WC-Ni [32][33][34][35][36][37][38][39][40][41], WC-Co-Ni [42], WC-Co-Cr [31,[43][44][45], or WC-Cu-MoS 2 [46,47]. Unfortunately, the carbides could not be used for PFCs and so we could not built on these results.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the Al 2 O 3 particles uniformly distributed inside the substrate, which exhibited low coefficient of friction (COF) and wear rate. Peat et al reported that the wear and erosion performances of a cold sprayed metal matrix composites (MMCs) were significantly improved after FSP. Yang et al used FSP to modify a cold sprayed AA2024/Al 2 O 3 MMCs, and stated FSP notably improved the refinement and dispersion of the Al 2 O 3 particles.…”
Section: Introductionmentioning
confidence: 99%